Data-Driven Manufacturing: Leveraging Analytics for Operational Excellence - Venkata Siva Prasad Maddala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of data-driven analytics on modern manufacturing operations, emphasizing its role in enhancing operational excellence and innovation. The article examines five key areas: production intelligence, supply chain optimization, sustainable manufacturing analytics, data-driven innovation, and implementation frameworks. Through detailed analysis, the article demonstrates how advanced analytics capabilities are revolutionizing manufacturing processes by enabling predictive maintenance, optimizing supply chains, promoting sustainable practices, and accelerating innovation cycles. The article reveals how manufacturing organizations leverage real-time monitoring, machine learning algorithms, and artificial intelligence to achieve improved operational efficiency, reduced maintenance costs, enhanced product quality, and increased market responsiveness. The article also addresses organizational readiness and technical infrastructure requirements for successfully implementing data-driven manufacturing solutions. By examining technical and organizational dimensions, this study provides valuable insights into how manufacturers can effectively transition to data-driven operations while maintaining competitive advantage in an increasingly dynamic market environment.
Keywords: Data-driven Manufacturing; Digital Transformation; Production Intelligence; Supply Chain Analytics; Sustainable Manufacturing